Management of Sialorrhea in People with Parkinson S Disease Through Behavioral Therapy and Thermotactile Stimulation [Manejo de la Sialorrea en Personas Con Enfermedad de Parkinson Mediante Terapia Conductivo Conductual y Estimulación Termo-Táctil] - Chana-Cuevas, P (Sociedad de Neurologia Psiquiatria y Neurocirugia, 2014)
This study proposes a Speech Therapy treatment for individuals with sialorrhea (saliva production perceived by patient as excessive) as a consequence of Parkinson Disease (PD). Method: A prospective study in 18 individuals with PD diagnosis was taken and divided into two groups: A) received only Cognitive Behavioral Therapy (CBT) (swallowing process awareness), while B) received CBT plus Thermal Tactile Stimulation (TTS) (cold sensory stimulation to the pharyngeal anterior pillars and oral cavity). The intervention lasted 5 weeks. The purpose of this research was to prove the effectiveness of Speech Therapy in dealing with sialorrhea and to assess a significant difference between CBT and CBT plus TTS. A t-student parameter test and the Mann-Withney test were used. Resulted: The assessment by the Clinical Scale for Parkinson Sialorrhea (SCS-PD) prior to therapy was CBT group was 2.6 and 11.5 ± 9.4 ± 4.2 group difference was not statistically significant. After therapy was 3.5 ± 2.8 and 4.6 ± 3.5 both showed a statistically significant difference compared to baseline (p < 0.001), not having statistically significant difference between them. Conclusion: These tests showed that both treatments are effective to decrease sialorrhea perception in individuals with PD. Nevertheless, no statistical significant differences were noted between both treatments.